2005
DOI: 10.1038/sj.eye.6702032
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on trypan blue capsule staining under air vs under viscoelastic

Abstract: Aim To compare the safety and effectiveness of trypan blue capsule staining under air vs under viscoelastic. Methods A total of 52 consecutive patients planned for phacoemulsification of white mature cataract were randomly assigned to trypan blue staining under air or under viscoelastic. Perioperative changes in bestcorrected visual acuity (BCVA), central corneal thickness (CCT), and endothelial cell density (ECD) were compared between the two groups. The differences in operating and phacoemulsification times,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…The mean loss of ECD after coaxial phacoemulsification for white mature cataract was reported to range from 8.5 to 18.6% at 3–6 months after surgery [1, 3, 5]. In our study, the mean ECD loss after MICS was 9.6% at 3 months postoperatively and was comparable with previous studies on coaxial phacoemulsification for white mature cataract.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The mean loss of ECD after coaxial phacoemulsification for white mature cataract was reported to range from 8.5 to 18.6% at 3–6 months after surgery [1, 3, 5]. In our study, the mean ECD loss after MICS was 9.6% at 3 months postoperatively and was comparable with previous studies on coaxial phacoemulsification for white mature cataract.…”
Section: Discussionsupporting
confidence: 80%
“…The median BCVA improved from hand movement preoperatively to 0.6 on day 1 postoperatively and all patients had a BCVA of 0.6 or better at 3 months postoperatively. The mean increase in CCT on day 1 postoperatively was 11.5% which is comparable to previous studies in which coaxial phacoemulsification was performed for mature cataract, with the mean increase in CCT ranging from 12.8 to 17% [1, 4, 5]. …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Recent studies have compared the efficacy and safety of these dyes [9][10][11][12][13][14]. Dada et al [12] compared Trypan Blue 0.1%, Gentian Violet 0.001%, ICG 0.5%, fluorescein 2%, and the patient's autologous blood for anterior capsular staining in cases of white cataracts.…”
Section: Review Of Recent Studiesmentioning
confidence: 99%
“…10 Techniques for capsule staining Different methodologies for injecting the dye have been described, including beneath air, 5,18 beneath ophthalmic surgical device (OVD), 19,20 beneath OVD and BSS, 21,22 and mixing with an OVD. 9,23, 16 Wong et al 24 found both methods equivalent.…”
Section: Dye-assisted Cataract Surgerymentioning
confidence: 99%